PROMISING AYURVEDIC HERBS IN THE MANAGEMENT OF KITIBHA (PSORIASIS)- A REVIEW - Krishna, *C. Murali; Kumar, D. Panchajanya; Sivaram, G.; S, Malini.; Venkateshwarlu, B.; P Dhoke, Sujata; Babu, G. (International Journal of Ayurveda and Pharma Research, 2018)
Psoriasis is one of the commonest skin disorders seen in routine clinical scenario, in entire world around 80 million people suffering from psoriasis. Psoriasis is differentiated by patches of abnormal skin. These skin patches are typically red, itchy, and scaly. Psoriasis varies in severity from small, localized patches to complete body coverage. It typically presents as red patches with white scales on top. Areas of the body most commonly affected are the back of the forearms, chin, navel area, and scalp. Diagnosis is typically based on the signs and symptoms. Men and women are affected with equal frequency. The disease may begin at any age, but typically starts in adulthood. Psoriasis is associated with an increased risk of psoriatic arthritis, lymphomas, cardiovascular disease and depression. Psoriatic arthritis affects up to 30 percent of individuals with Psoriasis. It is noted that around 2% of population are touching with Psoriasis. In present study review on Herbs frequently used in treating psoriasis were compiled. The Herbs Nimba, Stri Kutaja, Guduchi, Daruharidra, Bhallataka Haritaki, Aragvadha, Amalaki, Karveera, Saptaparna, Khadira, Vasa, Guggulu, Chitraka & Katuki are reviewed to be having Vata or Kapha balancing properties. The pharmacological studies showing that Nimbidin of Neem having anti psoriatic property, The Methanolic and ethanolic extracts of Stri Kutaja and Guduchi are having anti oxidant and anti psychotic properties which are helpful in reducing the symptoms of psoriasis.